Racial disparity in distant recurrence‐free survival in patients with localized breast cancer: A pooled analysis of National Surgical Adjuvant Breast and Bowel Project trials. Issue 14 (17th May 2022) - Kim, Gina; Pastoriza, Jessica M.; Qin, Jiyue; Lin, Juan; Karagiannis, George S.; Condeelis, John S.; Yothers, Greg; Anderson, Stewart; Julian, Thomas; Entenberg, David; Rohan, Thomas E.; Xue, Xiaonan; et al.
Abstract : Background: Black race is associated with worse outcome in patients with breast cancer. The distant relapse‐free survival (DRFS) between Black and White women with localized breast cancer who participated in National Cancer Institute–sponsored clinical trial was evaluated. Methods: Pooled data were analyzed from 8 National Surgical Adjuvant Breast and Bowel Project (NSABP) trials including 9702 women with localized breast cancer treated with adjuvant chemotherapy (AC, n = 7485) or neoadjuvant chemotherapy (NAC, n = 2217), who self‐reported as Black (n = 1070) or White (n = 8632) race. The association between race and DRFS was analyzed using log‐rank tests and multivariate Cox regression. Results: After adjustment for covariates including age, tumor size, nodal status, body mass index and taxane use, and treatment (AC vs NAC), Black race was associated with an inferior DRFS in estrogen receptor–positive (ER+; hazard ratio [HR], 1.24; 95% CI, 1.05‐1.46; P = .01), but not in ER– disease (HR, 0.97; 95% CI, 0.83‐1.14; P = .73), and significant interaction between race and ER status was observed ( P = .03). There was no racial disparity in DRFS among patients with pathologic complete response (pCR) (log‐rank P = .8). For patients without pCR, Black race was associated with worse DRFS in ER+ (HR, 1.67; 95% CI, 1.14‐2.45; P = .01), but not in ER– disease (HR, 0.91; 95% CI, 0.65‐1.28; P = .59). Conclusions: Black race was associated with significantly inferior DRFS in ER+ localized breast cancer treated with AC or NAC, but not in ER– disease. In the NAC group, racial disparity was also observed in patients with residual ER+ breast cancer at surgery, but not in those who had pCR. Lay Summary: Black women with breast cancer have worse outcomes compared with White women. We investigated if this held true in the context of clinical trials that provide controlled treatment setting. Black women with cancer expressing estrogen receptors (ERs) had worse outcome than White women. If breast cancers did not express ERs, there was no racial disparity in outcome. We also observed racial disparity in women who received chemotherapy before their cancer was removed, but only if they had cancer expressing ERs and residual disease on completion of treatment. If the cancer disappeared with presurgical chemotherapy, there was no racial disparity. Abstract : Data from 8 National Surgical Adjuvant Breast and Bowel Project clinical trials show that Black women have a significantly inferior distant relapse‐free survival in estrogen receptor–positive (ER+) localized breast cancer treated with adjuvant or neoadjuvant chemotherapy, but not in ER– disease. The most significant racial disparity was observed in patients with residual ER+ breast cancer at surgery, but not in those who had a pathologic complete response.